Subjective Well-being Individu dalam Rumah Tangga Di Indonesia - Aryogi, Ista; Wulan Sari, Dyah (Jurnal Ilmu Ekonomi Terapan, 2016)
Well-being is multi-dimensional development goals because well-being can not be seen only from individual income, but also the entire condition such as health and education. Complexities in measuring well-being made economists try to measure the individual well-being with subjective well-being approach. One of subjective well-being's variable is the happiness. This study aims to examine the factors determining the individual happiness in Indonesia. Those factors consist of per capita expenditure, personal assets, and individual characteristics, including yearly working hours, years of schooling, health status, marital status, age, and gender. This study uses logistic and probit regression. Object of this study is the individuals in household based on SUSENAS's representation that was obtained from Indonesia Family Life Survey in 2007. This research found that income is stil being main determinant of individual happiness. Significant results also were found in the variables of schooling, health status, marital status, and u-shaped in age. From these results, increasing income through various sectors of the economy is needed to reach a higher level of well-being. Health and education should also receive support through infrastructure improvements. Thus, there will be more people that are able to improve their well-being.